1998
DOI: 10.1002/(sici)1097-0134(19981101)33:2<285::aid-prot11>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamic properties of the single disulfide-deficient α-amylase inhibitor [C45A/C73A]tendamistat: An NMR study

Abstract: Covalent linkages such as disulfide bonds are important for the stabilization of proteins. In the present NMR study we compare the structure and the dynamics of the single disulfide-deficient variant C45A/C73A of the alpha-amylase inhibitor tendamistat and the wild-type protein, which contains two disulfide bonds (C11-C27 and C45-C73). Complete proton assignment was achieved by standard homonuclear 2D techniques for the variant. Chemical shift differences, intra-strand NOE effects and protected amide proton we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…That is, in mutants M 1 and M 2 , only one disulfide bond is kept, and in mutant M 3 , both disulfide bonds are removed. In our theoretical study, the native structures of these three mutants are obtained by energy minimization based on the wild-type native structure; this takes into consideration in experiment that their native structures were observed to be similar to the wild type (28). The energy minimization is realized by using Amber software (version 7.0) (39) after the replacements of the related residues (17).…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, in mutants M 1 and M 2 , only one disulfide bond is kept, and in mutant M 3 , both disulfide bonds are removed. In our theoretical study, the native structures of these three mutants are obtained by energy minimization based on the wild-type native structure; this takes into consideration in experiment that their native structures were observed to be similar to the wild type (28). The energy minimization is realized by using Amber software (version 7.0) (39) after the replacements of the related residues (17).…”
Section: Model and Methodsmentioning
confidence: 99%
“…It is an all-b-sheet protein with 74 amino acids and has two disulfide bonds (25,26). It has been well studied in a number of experiments (16,17,19,20,(27)(28)(29)(30). It was found that protein tendamistat exhibits a two-state folding behavior that has not been found in any other disulfidebonded proteins up to now.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In practice, however, this desirable effect is sometimes foiled by strain or reduced dynamics imposed on the native state, especially in the case of artificially introduced disulfide bonds. [3][4][5] Even though disulfide bridges are one of the best understood factors stabilizing the native structure of a protein, [6][7][8] their kinetic role in protein folding is not comprehensively understood. Disulfide bonds can lead to the persistence of partially structured or at least conformationally restricted regions in otherwise unfolded polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many studies involving removal of natural disulfide links (Schwartz et al 1987; Pace et al 1988; Eigenbrot et al 1990; Cooper et al 1992; Ikeguchi et al 1992; Kuroki et al 1992; Vogl et al 1995; Bonander et al 2000; Klink et al 2000) and insertion of novel ones (Sauer et al 1986; Wells and Powers 1986; Pantoliano et al 1987; Villafranca et al 1987; Pjura et al 1990; Takagi et al 1990; Matsumura and Matthews 1991; Clarke and Fersht 1993; Clarke et al 1995; Hinck et al 1996; Johnson et al 1997; Futami et al 2000), including those made by chemical modification (Goldenberg and Creighton 1983; Lin et al 1984; Ueda et al 1985), our understanding of the mechanism of stabilization of proteins by cross‐links is far from complete. Loop length alone does not fully account for observed changes in denaturation free energy or entropy (Zhang et al 1994; Vogl et al 1995; Balbach et al 1998) Disulfide mutants show decreased as well as increased stabilities, and their denaturation thermodynamic parameters do not support the Doig and Williams model (Matsumura and Matthews 1991; Johnson et al 1997).…”
mentioning
confidence: 99%
“…Steric and electrostatic effects of the amino acid side‐chains that replace the disulfide bond are believed to influence protein stability (Vogl et al 1995; Balbach et al 1998). Theoretical studies indicate that destabilization by a cross‐link can occur through reduction of configurational entropy of the folded state (Tidor and Karplus 1993).…”
mentioning
confidence: 99%